Digitalization and Financial Literacy for Ecoprint MSMEs, Based on Community Partnership Empowerment - A.Aviv Mahmudi; Dian Anita Sari; Wulandari Dyah Pitaloka; Nita Sari; Abdul Hamim Jazuli; Sayyidati Nafisah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The technological transformation in the digital era has reshaped the landscape of Micro, Small, and Medium Enterprises (MSMEs), presenting an opportunity to enhance competitiveness. Digitalization enables MSMEs to optimize operations and marketing through online platforms, expand market reach, and improve financial management. Financial literacy becomes an essential foundation for efficiently managing finances, assisting entrepreneurs in making strategic decisions. This article discusses the application of digitalization and financial literacy to ecoprint MSMEs in Lasem, Rembang, with a community empowerment approach. Through training that involves the use of social media, e-commerce, and financial applications, participants are expected to overcome challenges in business management. This initiative aims to create a collaborative ecosystem to support MSME growth, improve managerial skills, and strengthen business sustainability.